2022
DOI: 10.1186/s12877-022-03586-3
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring person-centred care in German nursing homes – exploring the construct validity of the Dementia Policy Questionnaire: a cross-sectional study of a secondary data set

Abstract: Background To ensure the sustainable implementation of dementia-specific person-centred care (PCC) in nursing homes, internal policies are crucial. The preliminary German Dementia Policy Questionnaire, which features 19 dichotomous items, assesses the existence of and evaluates these policies. This article reports the results of an exploration of the construct validity of the preliminary Dementia Policy Questionnaire. Methods This study is a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…After publication of this article [ 1 ], the authors reported that the author name ‘Hoffmann’ was incorrectly written as ‘Hoffman’. Moreover, In the Results section citations to references [24] and [25] were mixed up.…”
mentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that the author name ‘Hoffmann’ was incorrectly written as ‘Hoffman’. Moreover, In the Results section citations to references [24] and [25] were mixed up.…”
mentioning
confidence: 99%